2008
DOI: 10.18388/abp.2008_3054
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bovine serum albumin glycated with glucose, galactose and lactose.

Abstract: The non-enzymatic reaction between reducing sugars and proteins, known as glycation, has received increased attention from nutritional and medical research. In addition, there is a large interest in obtaining glycoconjugates of pure well-characterized oligosaccharides for biological research. In this study, glycation of bovine serum albumin (BSA) by d-glucose, d-galactose and d-lactose under dry-heat at 60 degrees C for 30, 60, 120, 180 or 240 min was assessed and the glycated products studied in order to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 34 publications
9
72
0
1
Order By: Relevance
“…13 When BSA was heated with Gal at 60 ∘ C for 120 min, seven glycated Lys residues (Lys-93, 116, 232, 261, 322, 350 and 396) were identified. 12 Glycated Lys residues (Lys-132 and Lys-136) are next to fluorophore Trp-134 in domain IB. Glycated Arg residue (Arg-217) is close to fluorophore Trp-213 in domain IIA.…”
Section: Bsa Residues Glycated With Xyl or Galmentioning
confidence: 99%
“…13 When BSA was heated with Gal at 60 ∘ C for 120 min, seven glycated Lys residues (Lys-93, 116, 232, 261, 322, 350 and 396) were identified. 12 Glycated Lys residues (Lys-132 and Lys-136) are next to fluorophore Trp-134 in domain IB. Glycated Arg residue (Arg-217) is close to fluorophore Trp-213 in domain IIA.…”
Section: Bsa Residues Glycated With Xyl or Galmentioning
confidence: 99%
“…Different sugar exhibit different reactivities. For example, pentose sugars (e.g., ribose) are more reactive than hexoses (e.g., glucose) due to their greater electrophilicity (Chevalier, Chobert, Genot, & Haertlé, ; Chevalier, Chobert, Popineau, Nicolas, & Haertlé, ; Laroque et al, ; Ledesma‐Osuna, Amos‐Clamont, & Vazquez‐Moreno, ). However, among hexoses, galactose is more reactive than glucose due to a higher steady state concentration of the reactive open chain form of galacotse than glucose (Cui, ).…”
Section: In Vitro and In Vivo Reduction Of Mrps Using Modified Carbohmentioning
confidence: 99%
“…Except for monosaccharides, the conjugation of carbohydrates to protein makes them susceptible to biological recognition by plant lectins (Blome & Schengrund, 2008;Ledesma-Osuna et al, 2008). ELLA assays were used to confirm that galactose residues were available from the produced neoglycans.…”
Section: Recognition Of Psa-lac By Soluble Lectin Assay (Ella Assays)mentioning
confidence: 99%
“…The early stage chemistry of non-enzymatic protein glycation involves an initial nucleophilic substitution reaction between sugar carbonyl groups and amino groups of proteins to form a Schiff´s base that undergoes spontaneous changes known as the Amadori rearrangement (Singh et al, 2001). Controlled and limited glycation at this point enables a direct attachment to protein without any prior modification or chemical activation of the reagents (Ledesma-Osuna et al, 2008). Sarabia-Sainz et al (2009) and Ledesma-Osuna et al (2008) demonstrated that lactosylated porcine serum albumin (PSA) neoglycans obtained by Maillard reaction interact with galactose-specific K88 adhesin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation